High heritability of malaria parasite clearance rate indicates a genetic basis for artemisinin resistance in western Cambodia. - Anderson, T; Nair, S; Nkhoma, S; Williams, J; Imwong, M; Yi, P; Socheat, D; Das, D; Chotivanich, K; Day, N; White, N; Dondorp, A (2010)
In western Cambodia, malaria parasites clear slowly from the blood after treatment with artemisinin derivatives, but it is unclear whether this results from parasite, host, or other factors specific to this population. We measured heritability of clearance rate by evaluating patients infected with identical or nonidentical parasite genotypes, using methods analogous to human twin studies. A substantial proportion (56%-58%) of the variation in clearance rate is explained by parasite genetics. This has 2 important implications: (1) selection with artemisinin derivatives will tend to drive resistance spread and (2) because heritability is high, the genes underlying parasite clearance rate may be identified by genome-wide association.